(untitled) (Docentes 2.0 Journal, 2022)
Over time, the conception of reading has changed and its processes and strategies. In ??the Spanish language, reading and writing are two terms that can be defined as pillars of education and are also nominated as human skills that allow discerning and shaping knowledge. The objective was to strengthen communication skills in students through the literary proposal of María Teresa Andruetto to encourage interest in reading various texts, which contributed to the consolidation of critical thinking and the formation of active subjects intellectually. The research was carried out under the humanistic paradigm, with a qualitative approach, action-research design, and a practical type. The population to which the proposal applied was a group of 12 students shown during each of the participatory classes and interested in books worked. A survey was conducted to collect information about the number of books read during the last year. The validation obtained arose from the analysis of each of the workshops designed for each session, and subsequently, triangulation was established with the instruments used for data collection. Finally, by applying reading comprehension strategies in children’s literature, it was possible to strengthen the levels of comprehension and incite interest in reading, thus achieving active subjects, with more possibilities in the consolidation of critical thinking.